Footprints in Time: what can three waves of data from the Australian longitudinal study of Indigenous children tell us about the development of Aboriginal and Torres Strait Islander children’s health and wellbeing? - Skelton, F (My University, 2012)
More than 1400 parents and carers of Indigenous children from across Australia were interviewed for Wave 3 Footprints in Time. This Australian Government funded study started in 2008 following two different age groups of Indigenous children from communities across Australia in urban, regional and remote areas. By Wave 3 in 2010, the younger group were aged around 3 years and the older group around 6 years. The answers given to the study’s Indigenous interviewers illustrate the diversity of experiences and attitudes held by Aboriginal and Torres Strait Islander children and their families. This presentation will use data from Waves 1, 2 and 3 to explore what helps Aboriginal and Torres Strait Islander children ‘grow up strong’, a key research question for the study. Both child and parent/carer social emotional wellbeing will be examined along with major life events and measures of resilience. Initial analyses indicate that parent/carer experiences of racism and lower levels of trust in the local school impact negatively on child learning outcomes. Exploration of preliminary Wave 3 Strengths and Difficulties data indicates increased difficulties scores are associated with greater numbers of major life events, experience of bullying and parental depression. These and other relationships will be examined further with the publically available Wave 3 data, including child health, level of isolation, parent/carer education and financial stress. Footprints in Time provides a unique opportunity to examine data from parents, teachers and the children themselves. In Wave 3 the older children were asked questions about school and their aspirations as well as completing vocabulary and school readiness assessments. The children’s responses will also be discussed in relation to their social and emotional wellbeing. The presentation aims to focus on the strengths of the Australian Indigenous children and families involved in the study and what is working well for Indigenous children’s health, development and wellbeing.
Keywords: Child Development -- Social; Child Development -- Emotional; Children -- Indigenous; Childhood and child development; Child Development; Children; Emotional; Social; Indigenous; Childhood and child development